Effects of orthography on production and perception of English initial consonant clusters by L1 Persian speakers - Bavandpour, Parisa Karimi (2014)
There are different views on how systems of speech perception and production function and if they are governed by the same system of rules and restrictions. The interrelation between learners’ perceptual and productive learning remains one of the central questions for investigation. This study investigated the influence of L1 orthography on Persian speakers’ production and perception of English initial consonant clusters. In contrast to English, word-initial consonant clusters do not occur in Persian. This structural difference between Persian and English may lead to L1interference and cause errors in the production and perception of L2 sounds. Previous studies reported that Persian speakers insert a vowel to break up the initial consonant clusters to comply with their L1 phonotactic rules. It was hypothesized that Persian speakers may depend on their first language orthography for reading in English and may produce more errors when faced with orthographic representation of words containing initial consonant clusters. In the perception of these clusters, Persian speakers were hypothesized to assimilate the consonant clusters to clusters containing vowels in order to adapt it to their native language phonology. To examine the production and perception of initial consonant clusters among Persian speakers and the effect of orthography, two production tasks and two perception tasks with different conditions were conducted. The first production task was a pseudoword repetition task with no orthographic representation and the second task was a pseudoword reading task with orthographic representation. The results from the speech production experiments showed fewer cases of vowel epenthesis when repeating the auditory stimuli, whereas, a significantly higher amount of vowel epenthesis occurred in reading the pseudowords. The results showed the inhibiting effect of orthography on speech production and its impact on the intelligibility of speech. In the perception tasks, there was an auditory task with no orthographic representation and an orthography task with orthographic representation. The results from the perception experiments showed significantly better performance with the visually presented pseudowords than the aurally presented pseudowords. In contrast to production, the findings suggest a facilitating effect of orthography on the perception of non-native consonant clusters. Persian speakers could create lexically contrastive representations for auditorily presented pseudowords containing initial consonant clusters when they were provided with visual support in the form of written forms. The results of the tasks showed that production and perception are not mirror images of one another, and are not governed by the same system of rules and restrictions.